2010
DOI: 10.1111/j.1365-2362.2010.02410.x
|View full text |Cite
|
Sign up to set email alerts
|

Autophagy as a mechanism for myolysis of cardiomyocytes in mitral regurgitation

Abstract: Induction of autophagy, but not oncosis, occurs in most cases of atrial cardiomyocytes with severe mitral and tricuspid regurgitation, even those without atrial fibrillation, and is closely associated with the development of myolysis in this disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 24 publications
1
27
0
Order By: Relevance
“…Ins(1,4,5)P 3 generation increases acutely under conditions of post-ischemic reperfusion [43] and chronically in dilated fibrosed atrial tissue from human and mouse [44]. Autophagy is increased in both of these circumstances, primarily as a protective mechanism [45][46][47]. It is possible that Ins(1,4,5)P 3 functions as an endogenous autophagy inhibitor under these pathological conditions.…”
Section: Discussionmentioning
confidence: 92%
“…Ins(1,4,5)P 3 generation increases acutely under conditions of post-ischemic reperfusion [43] and chronically in dilated fibrosed atrial tissue from human and mouse [44]. Autophagy is increased in both of these circumstances, primarily as a protective mechanism [45][46][47]. It is possible that Ins(1,4,5)P 3 functions as an endogenous autophagy inhibitor under these pathological conditions.…”
Section: Discussionmentioning
confidence: 92%
“…There is ongoing debate about whether autophagy plays a beneficial or detrimental role in cardiac diseases . Excessive autophagy contributed to age‐related cardiac disease development, including heart failure, hypertension‐induced cardiac diseases, mitral regurgitation, and diabetic cardiomyopathy . Interestingly, all these cardiac diseases are recognized to represent a substrate for AF, suggesting a role for autophagic activation in AF development.…”
Section: Discussionmentioning
confidence: 99%
“…Autophagy is widely involved as a cell‐stress pathway, whose excessive activation triggers cardiac remodeling in response to degradation of essential proteins and organelles. Activation of autophagy in the heart is implicated in cardiac remodeling in mitral regurgitation and cardiac hypertrophy …”
Section: Introductionmentioning
confidence: 99%
“…Similarly, time and AMPK‐dependent autophagy were found in canine model of AF . In another study, enhanced autophagy was found in atria originated from patient suffering from mitral regurgitation in the presence or absence of AF . However, in the aforementioned studies, the functionality of autophagic process was not studied.…”
Section: Autophagy Diabetic Cardiomyopathy and ‘Biotherapeutic’ Treamentioning
confidence: 98%